Frequency, mutual exclusivity and clinical associations of myositis autoantibodies in a combined European cohort of idiopathic inflammatory myopathy patients. (July 2019) - Betteridge, Z.; Tansley, S.; Shaddick, G.; Chinoy, H.; Cooper, R.G.; New, R.P.; Lilleker, J.B.; Vencovsky, J.; Chazarain, L.; Danko, K.; Nagy-Vincze, M.; Bodoki, L.; et al.
Abstract: Objectives: To determine prevalence and co-existence of myositis specific autoantibodies (MSAs) and myositis associated autoantibodies (MAAs) and associated clinical characteristics in a large cohort of idiopathic inflammatory myopathy (IIM) patients. Methods: Adult patients with confirmed IIM recruited to the EuroMyositis registry (n = 1637) from four centres were investigated for the presence of MSAs/MAAs by radiolabelled-immunoprecipitation, with confirmation of anti -MDA5 and anti -NXP2 by ELISA. Clinical associations for each autoantibody were calculated for 1483 patients with a single or no known autoantibody by global linear regression modelling. Results: MSAs/MAAs were found in 61.5% of patients, with 84.7% of autoantibody positive patients having a sole specificity, and only three cases (0.2%) having more than one MSA. The most frequently detected autoantibody was anti -Jo-1 (18.7%), with a further 21 specificities each found in 0.2–7.9% of patients. Autoantibodies to Mi-2, SAE, TIF1, NXP2, MDA5, PMScl and the non-Jo-1 tRNA-synthetases were strongly associated (p < 0.001) with cutaneous involvement. Anti -TIF1 and anti -Mi-2 positive patients had an increased risk of malignancy (OR 4.67 and 2.50 respectively), and anti -SRP patients had a greater likelihood of cardiac involvement (OR 4.15). Interstitial lung disease was strongly associated with the anti -tRNA synthetases, anti -MDA5, and anti -U1RNP/Sm. Overlap disease was strongly associated with anti -PMScl, anti -Ku, anti -U1RNP/Sm and anti -Ro60. Absence of MSA/MAA was negatively associated with extra-muscular manifestations. Conclusions: Myositis autoantibodies are present in the majority of patients with IIM and identify distinct clinical subsets. Furthermore, MSAs are nearly always mutually exclusive endorsing their credentials as valuable disease biomarkers. Highlights: Myositis specific autoantibodies very rarely coexist in the one individual allowing endotypes to be more precisely defined. The association of anti -TIF1 and cancer-associated myositis is confirmed with a cut-off age of over 58 years. In a large combined European myositis cohort associations of anti -SRP with carditis and anti -Mi-2 with cancer have emerged. Myositis associated autoantibodies are strongly associated with having myositis in association with another connective tissue disease.